2021
DOI: 10.1038/s41438-021-00487-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined genomic, transcriptomic, and metabolomic analyses provide insights into chayote (Sechium edule) evolution and fruit development

Abstract: Chayote (Sechium edule) is an agricultural crop in the Cucurbitaceae family that is rich in bioactive components. To enhance genetic research on chayote, we used Nanopore third-generation sequencing combined with Hi–C data to assemble a draft chayote genome. A chromosome-level assembly anchored on 14 chromosomes (N50 contig and scaffold sizes of 8.40 and 46.56 Mb, respectively) estimated the genome size as 606.42 Mb, which is large for the Cucurbitaceae, with 65.94% (401.08 Mb) of the genome comprising repetit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 107 publications
3
44
0
Order By: Relevance
“…The total length of the final chromosome-level genome was 582 Mb, ∼91.65% of the estimated genome size, which is similar to that of Sechium edule (i.e. 606 Mb) 39 but larger than those of other members of the Cucurbitaceae family, such as C. sativus , 40 C. melo , 41 and S. grosvenorii. 42 The genome assembly comprised 1,232 contigs and had a scaffold N50 of 50.78 Mb.…”
Section: Resultsmentioning
confidence: 76%
“…The total length of the final chromosome-level genome was 582 Mb, ∼91.65% of the estimated genome size, which is similar to that of Sechium edule (i.e. 606 Mb) 39 but larger than those of other members of the Cucurbitaceae family, such as C. sativus , 40 C. melo , 41 and S. grosvenorii. 42 The genome assembly comprised 1,232 contigs and had a scaffold N50 of 50.78 Mb.…”
Section: Resultsmentioning
confidence: 76%
“…Transcriptomics and metabolomics are used to investigate the sequence information and metabolite changes in different tissues/organs or the same tissues/organs at the different developmental stages. In 2021, the transcriptome and metabolome of the fruits at different developmental stages of S. edule were established, and the results revealed that the genes involved in fruit texture, pigment, flavor, flavonoids, antioxidants, and plant hormones are expressed at different levels during chayote fruit development (Fu et al, 2021). To our knowledge, this transcriptome and metabolome are the first ones reported for the S. edule plant.…”
Section: Omics Researchmentioning
confidence: 91%
“…With the advent of functional genomic research, the genome sequencing of the plants has been substantially accelerated, and a large amount of data has been generated (Morozova and Marra, 2008;Ondov et al, 2008). As an important squash vegetable, genomic, transcriptomic, and metabolomic analyses of the S. edule plant have been generated (Fu et al, 2021). A high-quality wholegenome sequence of S. edule with a size of 606.42 Mb has been completed.…”
Section: Omics Researchmentioning
confidence: 99%
“…Meanwhile, the low coverage (hundreds detected versus thousands predicted) of targeted metabolomics over the metabolome of given plant organisms has lessened the efficacy relative to uncovering the metabolic pathways and underlying genes. Given this, we have developed a widely targeted metabolomics method that combines merits from both targeted and untargeted metabolomics ( Chen et al., 2013 ), which has been successfully utilized in numerous species ( Chen et al., 2014 ; Wen et al., 2014 ; Song et al., 2015 ; Geng et al., 2016 ; Li et al., 2017 , 2021a ; Wang et al., 2017 ; Ghareeb et al., 2018 ; Cao et al., 2019 ; Lee et al., 2020 ; Liu et al., 2020 ; Zeng et al., 2020 ; Fu et al., 2021 ; Nie et al., 2021 ). By applying this protocol, we are now able to detect some 5000 metabolites from bread wheat samples within a single run that typically takes 20 min (data not published).…”
Section: Genetic Statistical Power and Metabolic Detection Capacity Need To Be Improved In Future Mgwas/mqtl Studiesmentioning
confidence: 99%